2015
DOI: 10.1089/mdr.2014.0070
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of ST131 Among CTX-M-ProducingEscherichia colifrom Community-Acquired Infections, in the Czech Republic

Abstract: A total of 2,683 nonrepetitive Escherichia coli isolates were collected from microbiological laboratories covering all regions of the Czech Republic, during April 2011. Antimicrobial susceptibility patterns of E. coli were assessed. All 38 cefotaxime-resistant (CTX-R) isolates were found to be extended-spectrum β-lactamase (ESBL)-positive by the double-disc synergy test. Thirty-two of those isolates produced enzymes of CTX-M-1 family, five of CTX-M-9 family, and one isolate both CTX-M types. Genotyping by mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…E. coli ST131 is a worldwide multidrug resistant clone responsible mainly for urinary but also for other types of infections and widely disseminated in hospital and community patients worldwide (Johnson et al, 2003; Cerquetti et al, 2010; Lee et al, 2010; Nicolas-Chanoine et al, 2014). In the Czech Republic, isolates of this ST producing CTX-M beta-lactamases were found in patients suffering from community or hospital acquired infections (Dolejska et al, 2012; Micenková et al, 2014; Papagiannitsis et al, 2015). Our results also pointed at the occurrence of CTX-M-15-producing ST131 clone in UHO.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli ST131 is a worldwide multidrug resistant clone responsible mainly for urinary but also for other types of infections and widely disseminated in hospital and community patients worldwide (Johnson et al, 2003; Cerquetti et al, 2010; Lee et al, 2010; Nicolas-Chanoine et al, 2014). In the Czech Republic, isolates of this ST producing CTX-M beta-lactamases were found in patients suffering from community or hospital acquired infections (Dolejska et al, 2012; Micenková et al, 2014; Papagiannitsis et al, 2015). Our results also pointed at the occurrence of CTX-M-15-producing ST131 clone in UHO.…”
Section: Discussionmentioning
confidence: 99%
“…Sonicated cell extracts were analyzed by IEF in polyacrylamide gels containing ampholytes (pH 3.5–9.5; AP Biotech, Piscataway, NJ). The separated β-lactamases were visualized by covering the gel with the chromogenic cephalosporin nitrocefin (0.2 mg/ml; Oxoid Ltd., Basingstoke, United Kingdom; Papagiannitsis et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Escherichia coli ST131 clone has been isolated from a diverse range of infections caused in community and hospitalized patients across the world (Dahbi et al, 2014;Papagiannitsis et al, 2015;Peirano et al, 2014;Wu et al, 2014). A recent French study showed the proportion of E. coli ST131 as an intestinal colonizing organism increased significantly over time, from 8 % in 2002 to 50 % in 2004 (Han et al, 2014).…”
Section: Introductionmentioning
confidence: 99%